2017
DOI: 10.1007/s10072-017-3069-4
|View full text |Cite
|
Sign up to set email alerts
|

Fixational eye movements in Tourette syndrome

Abstract: Studies of saccadic eye movements in subjects with Tourette syndrome (TS) have provided additional evidence that there is a link between TS symptoms and deficits in fronto-striato-thalamic networks. These studies revealed impaired timing and inhibition of saccades. We compared fixational eye movements, such as microsaccades and ocular drifts, in subjects with TS and healthy controls.We measured horizontal and vertical eye positions with video-oculography in 14 subjects with Tourette syndrome. We found reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A recent study found patients with Tourette syndrome to have reduced microsaccade amplitudes and increased intersaccadic intervals, along with increased fixation instability and drift velocities ( 29 ).…”
Section: Microsaccades In Neurological Diseasementioning
confidence: 99%
“…A recent study found patients with Tourette syndrome to have reduced microsaccade amplitudes and increased intersaccadic intervals, along with increased fixation instability and drift velocities ( 29 ).…”
Section: Microsaccades In Neurological Diseasementioning
confidence: 99%